GENDER-RELATIVE EFFECT OF PROJECT-BASED LEARNING METHOD ON ACADEMIC ACHIEVEMENT AND RETENTION OF TECHNICAL COLLEGE STUDENTS IN BASIC ELECTRICITY (NAU Journal of Technology and Vocational Education, 2024)
The gender-related controversies associated with effects of various teaching methods gave riseto this study. This study was conducted to ascertain the gender-relative effect of project-basedlearning method on academic achievement and retention of technical college students in BasicElectricity. The study was carried out in Anambra state and adopted the quasi-experimentalresearch design. This was precisely, pretest, posttest, delayed posttest non-randomized controlgroup design which involved groups of students in their intact classes. A sample of 92 NTC IIstudents was drawn from a population of 179 students of state owned technical colleges inAnambra state. Two research questions and two null hypotheses tested at 0.05 level ofsignificance guided the study. Basic Electricity Achievement Test (BEAT), a 40-item multiplechoice test which was based on the units covered in the study, served as the instrument used fordata collection. The BEAT and lesson plans for both control and experimental groups were allvalidated by three experts from the faculty of education, Nnamdi Azikiwe University Awka. Thereliability coefficient of the instrument was found to be 0.82 using KR-20. Mean and standarddeviation were used to answer the research questions, while Analysis of Covariance (ANCOVA)was employed to test the hypotheses. Findings revealed that male and female technical collegestudents taught Basic electricity using project-based learning method had higher achievementand retention scores than those taught using the conventional teaching method. Also findingsrevealed that there was no significant difference in the mean achievement and retention scoresof the male and female students taught basic electricity using PBLM. Based on the findings ofthis study, it was concluded that PBLM has the potential to improve male and female technicalcollege students’ academic achievement and retention in Basic electricity. Consequently, it wasrecommended among others that Basic electricity teachers should use PBLM in the teaching ofBasic electricity and grant students equal opportunity during classroom instructions irrespectiveof gender so as to enhance students’ academic achievement and retention in the subject.
Keywords: Gender, Project-based learning, Academic achievement, Retention, Basic Electricity, Technical colleges